Seismic protection of land-based wind turbine towers using the tuned inerter damper. (May 2023) - Alotta, Gioacchino; Biondo, Chiara; Giaralis, Agathoklis; Failla, Giuseppe
Abstract: The tuned inerter damper (TID) has recently emerged in the literature as a bona fide resonant vibration absorber for the seismic protection of building structures by relaxing the requirement for large secondary mass employed in conventional tuned mass dampers (TMDs). This is achieved by leveraging the inertia property of lightweight inerter devices, called inertance. This paper extends the application of the TID to address the seismic response reduction of the supporting towers of land-based wind turbines (WTs). To this aim, a novel vibration suppression strategy is proposed for WT towers in which a TID is attached at two different locations inside and along the height of the tower and is tuned to the tower's dominant natural frequency. Numerical assessment is supported by developing a finite-element model of the benchmark NREL 5 MW WT equipped with an ad hoc TID model placed at different locations in the tower and with different inertance values. The assessment includes time-domain response history analyses for 28 earthquake ground motions (GMs) with and without pulses under concurrent thrust wind forces for 4 different mean wind speeds. Improved TID vibration suppression performance is noted by installing the TID closer to the tower top and by increasing the inertance and/or the distance of the attachment locations. Further, the TID achieves significant reductions of tower top peak displacement and acceleration as well as peak base shear and bending moment for all the different combinations of GMs and wind speeds, outperforming a conventional TMD with 5% secondary mass ratio placed in the nacelle.